EVALUASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI KELURAHAN ROWOSARI, KECAMATAN TEMBALANG, KOTA SEMARANG - Muliya Rahmayanti; Kismartini Kismartini; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
PNPM Mandiri is a national program run by all citizens to reduce poverty and expanding employment opportunities through efforts to improve community empowerment and independency in the purpose of enhancing the quality of life and the level of public welfare. The community itself is the main player. This evaluation is needed to see the results of this policy, as well as the supporting and inhibiting factors of the implementation by using William Dunn’s policy evaluation indicators and community empowerment according to mardikanto, it is the effectiveness of, sufficiency , the accuracy of , participatory , transparency and accountability . Evaluation of PNPM in Sub Rowosari that in the evaluation indicators, three of which are still considered not a maximum that is based on the effectiveness, adequacy and participatory.Meanwhile, the assessment of the evaluation indicators which is considered as good are in the accuracy, transparency and accountability. However, the obstacle of this program is the lack of participation and knowledge of the community to the PNPM Mandiri which make the unsatisfying outcomes of the program itself. Modernization and the existence of self-inteest are also the inhibiting factors of this program. The results of these studies indicate that the program has been successful in Sub Roworasi but not maximal. The recommendation for this program like socializing more evenly, programs do not always on physical development, attempt to follow the development, sanction for community groups who have certain interests, the need for monitoring and assisting in community groups routinely.